SOCIAL BACKGROUND OF CAREER GUIDANCE SYSTEM: RETROSPECTIVE ANALYSIS - E. Dianina (Вестник университета)
The paper analyzes the social conditions of formation and development of professional orientation activities. Considered periods: ancient civilizations (Ancient Egypt, Babylon, China), antiquity The Middle Ages, the period of the First World War, Europe and the United States in the XIX and XX century. And also highlighted the methods and principles of career guidance in these historical periods.